2015
DOI: 10.1186/s12872-015-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners’ vitamin K antagonist monitoring is associated with better blood pressure control in patients with hypertension – a cross-sectional database study

Abstract: BackgroundPatients requiring anticoagulation suffer from comorbidities such as hypertension. On the occasion of INR monitoring, general practitioners (GPs) have the opportunity to control for blood pressure (BP). We aimed to evaluate the impact of Vitamin-K Antagonist (VKA) monitoring by GPs on BP control in patients with hypertension.MethodsWe cross-sectionally analyzed the database of the Swiss Family Medicine ICPC Research using Electronic Medical Records (FIRE) of 60 general practices in a primary care set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Nevertheless, it must be acknowledged that periodical INR monitoring required under VKA treatment imposes not necessarily a burden for patients and primary physicians. A recent study suggested that it could also enhance patient-physician relation and therapy adherence and offer opportunities for the physician to provide additional care to patients, such as adjusting the dosage of antihypertensive drugs, giving smoking cessation advice or treating high cholesterol [93]. Our findings now show that concomitant comprehensive care for other conditions does not impair physicians' resources in controlling INR and ensuring high quality TTR control.…”
Section: Strength and Limitationssupporting
confidence: 48%
See 1 more Smart Citation
“…Nevertheless, it must be acknowledged that periodical INR monitoring required under VKA treatment imposes not necessarily a burden for patients and primary physicians. A recent study suggested that it could also enhance patient-physician relation and therapy adherence and offer opportunities for the physician to provide additional care to patients, such as adjusting the dosage of antihypertensive drugs, giving smoking cessation advice or treating high cholesterol [93]. Our findings now show that concomitant comprehensive care for other conditions does not impair physicians' resources in controlling INR and ensuring high quality TTR control.…”
Section: Strength and Limitationssupporting
confidence: 48%
“…A recent study suggested that it could also enhance patient-physician relation and therapy adherence and offer opportunities for the physician to provide additional care to patients, such as adjusting the dosage of antihypertensive drugs, giving smoking cessation advice, or treating high cholesterol. 93 Our findings now show that concomitant comprehensive care for other conditions does not impair physicians' resources in controlling INR and ensuring high-quality TTR control. This is of particular relevance for daily practice in primary care worldwide, given the high prevalence of multimorbidity in primary care patients.…”
Section: Strengths and Limitationsmentioning
confidence: 53%
“… in-house IT and pharmaco-epidemiologist teams No private-sector company GRAPHC - Australian National University - A ustralian Primary Health Care Research Institute [ 182 ] Canning Division of General Practice Australian General Practice Network MEGPN Independent accredited not-for-profit organization [ 27 ] PCS Clinical Audit Tool© Practice Health Atlas© Intego a Flemish government, Department of Health Care [ 54 ] - Department of General Practice of the KU Leuven [ 54 ] - Other universities. - GPs’ participation in the ethics and scientific committee - Datasoft, Medidoc - Careconnect EHR - No private-sector company involved in data analysis NIHDI Public social security institution [ 23 ] Extraction module on EHR [ 23 ] Health Search Database / CSD© Cegedim © [ 77 ] Swedestar project - Department of Medical and Health Sciences, University of Linköping, Unit of Research and Development in Primary Care, Jönköping - Lindsdals Primary Health Centre [ 96 ] Swedestar software [ 96 ] FIRE - Institute of General Practice of Zurich University [ 97 ] - “SGAM informatics”, a study group of the Swiss Association of GPs [ 26 ] Grhanite extracting tool LPD network - Cegedim Doc’ware software - Cegedim © [ 8 ] a the contact person gave information on the project governance following our enquiry by email …”
Section: Resultsmentioning
confidence: 99%